Enhancing vaccine clinical trials participation among elderly: challenges and strategies - Paul Gillard; Samer Nakhle; Darin Brimhall; Ouzama Henry; Narcisa Mesaros (Trials)
Abstract As the fastest growing demographic worldwide, the elderly population is projected to reach nearly 1 billion by 2030 and double the 2022 number by 2050. Despite being the largest consumers of medications, they have been historically underrepresented in clinical trials. However, we are witnessing a promising shift as their participation in trials is on the rise. In fact, recent megatrials enrolling more than 30,000 elderly participants demonstrated the feasibility of large-scale clinical trials involving this very specific population. However, unique challenges, including multi-morbidities, frailty, and ethically sound informed consent in those with cognitive deficits, require continuous careful reassessments and flexibility. Creative and tailored strategies are of paramount importance to bolster elderly trial participation. This paper highlights challenges and shares our experiences on novel methods and success stories associated with the enrollment and retention of elderly individuals in clinical trials. Successful tactics to balance the burden of clinical trial participation with its benefits encompass regular contact, family and friends’ engagement, making travel easier or unnecessary, use of digital tools, and building relationships with community organizations. Through innovative strategies that consider the unique needs and limitations of this population, we can achieve successful participation in clinical trials. This will lead to more effective treatments and interventions for our growing elderly population.